Peran Ulama Abad Xix Dalam Mengembangkan Pesantren Di Indonesia: Studi Atas Pemikiran Abdurrahman Mas’ud Tentang Pendidikan Pesantren - M Thoyyib (Al Hikmah: Jurnal Studi Keislaman, 2019)
Abstract. The existence of the Islamic education system today cannot be separated from the influence of ulama XIX century. Ulama in the XIX century had a strong network with Haramayn. Haramayn is a very strategic learning place. In the XIX century many ulama learned to Haramayn. When the ulama returned to their homeland, they established a pesantren as a place to spread the knowledge they had acquired. Therefore, pesantren and ulama have a very close relationship in developing the Islamic education system in Indonesia. This study uses literature study and uses qualitative descriptive analytical methods. Qualitative descriptive analysis method is a research model that emphasizes reasoning, and search and is supported by related data and literature. The results of this study indicate that there are six major ulama who have strong influence to develop pesantren. Three of whom are representatives of ethnic groups in Indonesia, Java, Sunda and Madura. Pesantren is also a strategic place to foster national values to its students, and pesantren are the basis of resistance for colonialist.Keyword: Ulama, Pesantren, Haramayn, Nusantara.